DIPLOMATIC ETIQUETTE, MEMO, CONFIDENCE AND STATECRAFT - Olimjonova Sevinchoy (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The article explores the role and importance of diplomatic etiquette. Diplomatic etiquette is a manifestation of good behavior in relations between officials, political and public figures representing their country. Diplomats interact with their counterparts in government, public, and business circles according to long-established rules, deviations from which can lead to unwanted complications in the relationship.The rules of diplomatic etiquette contain certain forms of addressing, correspondence, as well as visits, meetings and talks, diplomatic receptions, etc.